2019
DOI: 10.3389/fpls.2018.01918
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Diversity of Beech Seedlings Under Climate Change Scenarios

Abstract: The ability of beech (Fagus sylvatica L.) populations to adapt to the ongoing climate change is especially important in the southern part of Europe, where environmental change is expected to be more intense. In this study, we tested the existing adaptive potential of eight beech populations from two provenances in N.E. Greece (Evros and Drama) that show differences in their environmental conditions and biogeographical background. Seedling survival, growth and leaf phenological traits were selected as adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 100 publications
(128 reference statements)
3
16
0
Order By: Relevance
“…In this study, we observed a high contribution of residuals to the variance in bud phenology, which is in agreement with previous studies (Sole-Medina et al 2020; Varsamis et al 2018). This large heterogeneity in phenology unexplained by our factors may suggest a high variability among individuals (Perrin et al 2017), in addition to the potential effect of microsite conditions and sampling errors during eld observations.…”
Section: Plasticity Vs Local Adaptationsupporting
confidence: 94%
“…In this study, we observed a high contribution of residuals to the variance in bud phenology, which is in agreement with previous studies (Sole-Medina et al 2020; Varsamis et al 2018). This large heterogeneity in phenology unexplained by our factors may suggest a high variability among individuals (Perrin et al 2017), in addition to the potential effect of microsite conditions and sampling errors during eld observations.…”
Section: Plasticity Vs Local Adaptationsupporting
confidence: 94%
“…Auxin-response factors have been shown to be involved in abiotic adaptation (e.g., precipitation/drought, bud burst) in different tree species [44][45][46][47], and it has been proposed that beech morphology is related to environmental conditions at its growing sites [7,17]. Furthermore, Varsamis et al [48] detected significant differences in adaptive traits such as bud burst timing and survival under drought conditions between beech populations from West and East Rodopi in a provenance test and a growth chamber experiment. Thus, this locus may be involved in adaptation in F. sylvatica and F. orientalis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not observe growth reduction, as LAR was still able to support both growth and storage, hence lethal carbon starvation could not be assumed. However, unlike trees in the canopy, young trees do not have the opportunity to replenish NSC reserves in autumn (Hoch et al, 2003) because leaf senescence of trees and regeneration occurs at same time (Varsamis et al, 2019;Vitasse et al, 2009). Therefore, the NSC reserves of young trees may decrease for decades, eventually leading to tree death.…”
Section: Traits Of Shade Tolerance and Their Impact On Survival Timementioning
confidence: 99%